ACKNOWLEDGEMENT PATTERNS IN RESEARCH ARTICLES: A BIBLIOMETRIC STUDY BASED ON JOURNAL OF NATURAL RUBBER RESEARCH 1986-1997* - W. S., Tiew; B.K., Sen (Malaysian Journal of Library and Information Science, 2002)
Analyses the acknowledgements included in the research articles and short communications published in Journal of Natural Rubber Research (1986-1997) in respect of types, frequency of occurrence, individuals acknowledged, etc. Results indicate that 74% items contain acknowledgements; an average acknowledgement per item is 2.2; the most common type of acknowledgments relates to technical support. Peer interactive communication accounts for 44% of the total acknowledgements. The result of the study substantiates the earlier findings that a small number of individuals are highly acknowledged and the rest are acknowledged infrequently.